Management of inheritance claims: issues and challenges of Amanah Raya Berhad Alor Setar / Muhammad Fakhrul Hadi Dzalihu’zzabir - Dzalihu'zzabir, Muhammad Fakhrul Hadi (2025)
Estate claims management is an important element in ensuring that the distribution of inheritance assets is done fairly and systematically, thereby ensuring the well-being of heirs and the economic stability of the community. This study examines the issues and challenges faced by Amanah Raya, especially at the Alor Setar branch, in managing estate claims. This study also aims to identify the main causes of these challenges and suggest improvements to increase the effectiveness and efficiency of management. Using a qualitative approach, data was obtained through in-depth interviews with Amanah Raya officers and heirs involved. The study findings show several key challenges, including complex bureaucratic processes, lack of public awareness of inheritance claim procedures, weaknesses in the use of digital technology, and constraints in cooperation with third-party agencies such as courts and land offices. These challenges not only slow down the resolution process, but also put pressure on heirs who deal with time-consuming and complicated procedures. As a recommendation, this study suggests the implementation of a fully digital system to facilitate the documentation and verification process, intensify public awareness campaigns through mass media channels and community programs, and strengthen coordination with third-party agencies through a more connected and efficient network system. The implications of this study indicate that these improvement measures can improve the smooth management of estate claims, reduce settlement time, and ensure fairness to all parties involved. The population in this study is officers involved in the management of inheritance claims at AmanahRaya Berhad, Alor Setar Branch, and the sample selected consists of five officers out of twelve people, using the simple random sampling technique. Overall, this study contributes to a deeper understanding of the issues and challenges in the management of estate claims in Amanah Raya as well as providing a basis for future research that can further strengthen the inheritance system in Malaysia.